2011
DOI: 10.1080/15205436.2011.615446
|View full text |Cite
|
Sign up to set email alerts
|

Structural Pluralism in Journalism and Media Studies: A Concept Explication and Theory Construction

Abstract: the article explicates structural pluralism as a multifaceted concept with multiple dimensions and indicators. While reviewing relationships or hypotheses between structural pluralism and various outcomes, the article then discusses and proposes issues and agendas for future studies.The authors are grateful to three anonymous reviewers and the guest editor for thier valuable comments and suggestions.Seungahn Nah (Ph.D., University of Wisconsin-Madison, 2006) is an Assistant Professor in the Department of Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…8 The community conflict and structural pluralism concepts have been tested by numerous communication researchers, often demonstrating predictive power. 9 Studies have used the framework to examine media coverage of social change 10 and political and youth participation, 11 as well as the role of community stress in public affairs place blogging. 12 These studies adapted structural pluralism into a broader discussion about community structure and the relationship between journalists and the contextual influences of the surrounding society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8 The community conflict and structural pluralism concepts have been tested by numerous communication researchers, often demonstrating predictive power. 9 Studies have used the framework to examine media coverage of social change 10 and political and youth participation, 11 as well as the role of community stress in public affairs place blogging. 12 These studies adapted structural pluralism into a broader discussion about community structure and the relationship between journalists and the contextual influences of the surrounding society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The community structuralism model has generated an enduring line of research spawned by the Minnesota trio several decades ago, but it remains understudied (Nah & Armstrong, 2011). Tichenor, Donohue, and Olien (1980) demonstrated that media reflect the power structure of the community served, with newspapers in larger, heterogeneous communities conveying conflict information that's functional for diversity, while smaller, homogeneous communities avoid upsetting the apple cart.…”
mentioning
confidence: 98%
“…For instance, to measure community structural pluralism, the traditional community structural pluralism studies conducted by Tichenor et al (1980) used the following indicators: city population, county population, county per-capita income, labor force not in agriculture, and distance from a major metropolitan area. However, due to the lack of clear operational definitions, there has been dearth of consistency as to what indicators are being used to measure the characteristics of community (Nah & Armstrong, 2011). For this study, operationally, community structure was measured in terms of two dimensions: structural pluralism (based on the traditional structural indicators) and ethnic diversity.…”
Section: Independent Variablementioning
confidence: 99%
“…& Abisaid, J. The influence of community structure on crime news coverage: structural pluralism, ethnic diversity, and local crime news demonstrated broad differences depending on the research topics and contexts (Nah & Armstrong, 2011). That is, no consistent or congruous way exists among researchers for measuring community structural pluralism based on past studies (see, e.g., Appendix of Jeffres, Cutietta, Sekerka, & Lee [2000: 183-184] and Table 1 of Nah & Armstrong [2011: 865-866] on this subject).…”
Section: Independent Variablementioning
confidence: 99%
See 1 more Smart Citation